Hubungan Penggunaan Media Pembelajaran Berbasis Teknologi Dengan Minat Belajar Anak Usia Dini - Maulida, Triana; Arsapermana, Saveria Shabrina Zahwa; Jayadinata, Asep Kurnia; Ardiyanti, Dhea; Putri, Hafiziani Eka; Zarifa, Siti Aliyyah; Shalwa, Azzahra (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
The use of technology-based learning media is a widely used strategy in early childhood education to support learning. This study aims to examine the relationship between the use of technology-based learning media and early childhood learning interest based on the perspective of early childhood teachers. The study uses a quantitative approach with an associative design. Data were collected using a four-point Likert-scale online questionnaire completed by 14 early childhood teachers in the Purwakarta and Bandung areas who actively use technology in learning. The research instrument was first tested for validity using corrected item–total correlations and for reliability using Cronbach’s alpha. Data analysis included the Kolmogorov–Smirnov normality test and Spearman’s correlation test. The analysis showed that all items in the instrument were valid and reliable. The Spearman correlation test yielded a correlation coefficient of 0.585 (p = 0.028; < 0.05), indicating a positive and significant relationship between the use of technology-based learning media and early childhood learning interest. These findings indicate an association between variations in technology use in learning and children’s interest in learning, as reflected in their attention, engagement, and enthusiasm during the learning process in a limited sample.